FILTRATION OF SALINE SOLUTIONS IN SOIL ENVIRONMENTS - Kuzlo, M. T.; Martyniuk, P. M. (Academic journal Industrial Machine Building Civil Engineering, 2017)
The regularities of saline solutions concentration influence and their temperature on soil filtration characteristics have been experimentally investigated, substantiated and established. Significant difference between the filtration coefficient of saline solutions, considering their temperature and filtration of pure water was found out. So, at the concentration of saline solutions from 0 to 40…80 g/l the filtration rate increases sharply. With the further increase in the concentration of saline solutions, there is a phenomenon of soil softening, which leads to sharp decrease in their permeability, and, consequently, the coefficient of filtration. Such a pattern can be explained on the basis of physical and chemical processes occurring between mineral particles (solid phase) and saline solutions (liquid phase). In this case, it is got disperse system. Any disperse system tries to reduce its surface energy. In the system of «mineral particles + solution» it can be diminished by both reducing the total surface size and the liquid the surface tension.